Principles of corporate finance - Brealey, Richard A.
Throughout Principles of Corporate Finance, Concise the authors show how managers use financial theory to solve practical problems and as a way of learning how to respond to change by showing not just how but why companies and management act as they do. The first ten chapters mirror the Principles text, covering the time value of money, the valuation of bonds and stocks, and practical capital budgeting decisions. The remaining chapters discuss market efficiency, payout policy, and capital structure, option valuation, and financial planning and analysis